An exhaustive research and analysis on seismic performance of prefabricated concrete shear wall structure - Shuzhen Chen (297742) (2020)
In order to accelerate the process of building industrialization, improve the overall stability and construction quality of the building. In this paper, a bolted connection method is designed to study the seismic performance of the composite concrete shear wall specimens with horizontal split joints from the aspects of bearing capacity, ductility, energy dissipation, deformation capacity and failure mode. The test results show that the bolted concrete shear wall is feasible and the connectors can effectively connect the upper and lower precast shear walls to form a whole with certain lateral stiffness. The energy dissipation capacity of the specimens is similar to that of other prefabricated concrete shear wall structures with “self-reduction”. The displacement Angle is greater than 1/120 of the limit value of the displacement Angle between elastic-plastic layers under the action of large earthquakes, and the specimen has good deformation capacity. The energy dissipation capacity of the structure from dynamics perspective reveals that smaller capacity of the specimen by providing energy dissipation factor E= 0.24 and equivalent viscous damping coefficient of 0.038. Other Information Published in: Journal of Vibroengineering License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.21595/jve.2020.21628